The Effect of Chatbots on Managing Brand Reputation among Commercial Banks in Kenya - Momanyi, Frankline; Mutwiri, Isaac; Wasiaya, Christopher (International Journal of Research in Interdisciplinary Studies, 2024)
Commercial banks in Kenya are facing increasing competition from non-bank financial institutions, such as mobile money operators and microfinance institutions. In order to maintain their market, share and reputation, banks need to find ways to improve customer service and engagement. Traditional customer support channels may be insufficient to meet the evolving expectations of tech-savvy customers in a digitally-driven era. The reliance on manual customer service processes, which can be time-consuming and prone to human error, may lead to delayed response times, inconsistent messaging, and inadequate handling of customer inquiries and complaints. This can negatively impact brand reputation, as customers value prompt and accurate support experiences. The general objective of this study was to assess the effect of chatbots on managing brand reputation among commercial banks in Kenya. Specifically, the study sought to examine the level of adoption and usage of chatbots among commercial banks in Kenya, to establish the effect of chatbot adoption on customer satisfaction among commercial banks in Kenya, to determine the effect of chatbot adoption on customer trust and confidence among commercial banks in Kenya, and to examine the effect of chatbot adoption on service quality among commercial banks in Kenya. This research was based on the diffusion of innovation theory and the technology acceptance model to explain the relationship between the study variables. A descriptive survey design was adopted. The target population included 34 out of 38 commercial banks operating in Kenya A census was conducted on all the 34 commercial banks. The unit of observation was 34 brand managers in each of the commercial banks and 384 bank customers. The bank customers were arrived at using stratified random sampling. Primary data was collected through structured questionnaires and was analyzed descriptively by use of means and standard deviation and inferentially by use of correlation and regression analyses using SPSS version 27. Data was presented in form of frequency tables. The overall level of adoption was great as indicated by a mean of 3.7 which was great among commercial banks. Linear regression results indicated, according to customer, chatbot adoption significantly accounted for 35.2% variation in customer satisfaction while for brand managers, it significantly accounted for 41.0%. According to customer, chatbot adoption significantly accounted for 28.1% variation in Customer trust and confidence while for brand managers, it significantly accounted for 39.3%. According to customer, chatbot adoption significantly accounted for 18.6% variation in service quality while for brand managers, it significantly accounted for 29.8%. The study concluded that adoption of chatbot has significant positive effect on the management of brand reputation indicators (customer satisfaction, service quality, customer trust and confidence). The study recommended that the bank should focus on optimizing chatbot integration across various touchpoints and channels to ensure a seamless customer experience. Bank management should empower customers with control over their data by providing tools and resources to manage their privacy settings, opt-in or opt-out of certain data collection practices, and monitor their account activity for any signs of suspicious behavior.